25+ years of ICT in policy documents for teacher education in Norway and Denmark (1992 to 2020): a study of how digital technology is integrated into policy documents. Issue 4 (2nd October 2021) - Arstorp, Ann-Thérèse
ABSTRACT: This paper examines the role of digital technology in national guidelines and regulations in Norwegian and Danish teacher education over the course of 28 years (1992–2020). These policy documents are used to examine policy perspectives on digital technology through an analytical framework based on Wartofsky's artifact categories. The analytical categories developed for this study are tool artifacts, teacher professional artifacts and discursive artifacts. The results show that the different categories dominate at different times. The Norwegian policy documents indicate an increase in teacher professional artifacts and a decrease in tool artifacts over time, whereas the Danish policy documents show the opposite tendency. Discursive artifacts are absent in Danish policy documents while their presence diminishes over time in the Norwegian policy documents. As teachers, and ITE in particular, are still struggling to realise educational policy aims, there is still a need for direction, this absence seems to run counter to the goal of increasing PDC in ITE.